2009
DOI: 10.1590/s0100-204x2009000600007
|View full text |Cite
|
Sign up to set email alerts
|

Controle genético do teor proteico nos grãos e de caracteres agronômicos em milho cultivado com diferentes níveis de adubação nitrogenada

Abstract: Resumo -O objetivo deste trabalho foi determinar o controle genético do teor de proteína em grãos e de caracteres agronômicos de milho (Zea mays) cultivado com diferentes níveis de adubação nitrogenada. Foram avaliados nove genitores de milho e seus híbridos, em dialelo completo, com dois níveis de adubação nitrogenada. Os caracteres avaliados foram: índice relativo de clorofi la, altura de plantas, altura de espigas, produção de espigas, produção de grãos, coloração de grãos, massa de cem grãos, densidade de … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 10 publications
0
4
0
2
Order By: Relevance
“…The economic importance of maize is due to the broad possibilities of use, in fresh or processed form. However, the development of increasingly productive maize hybrid varieties resulted in a loss of nutritional value, especially with decreases in protein and oil, due to the negative correlation with yield (Uribelarrea et al 2004, Zhang et al 2008, Bueno et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…The economic importance of maize is due to the broad possibilities of use, in fresh or processed form. However, the development of increasingly productive maize hybrid varieties resulted in a loss of nutritional value, especially with decreases in protein and oil, due to the negative correlation with yield (Uribelarrea et al 2004, Zhang et al 2008, Bueno et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Using leaf chlorophyll has the advantage of being a viable technique that is able to predict N nutritional level, according to Booij et al (2000), since its quantity seems positively correlated with the nutrient. According to Godoy et al (2007) and Bueno et al (2009), determination of the leaf chlorophyll is sufficiently sensitive to the variations in nitrogen supply in dry material or coming from the fertilizer, thus enabling quicker detection of N deficiency. Carvalho et al (2003) observed good perspectives for preventing N deficiency in the beans with the aid of a chlorophyll measuring device, as well as the viability of adequately correcting lack of N. Results have indicated the need for various collections of samples throughout the plant's life cycle in order to determine the variations in chlorophyll content and its relationship with leaf N levels (Waskon et al, 1996;Zebarth et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Tais resultados estão em concordância com aqueles obtidos por Bueno et al (2009) e Silva et al (2015, que também verificaram comportamento diferencial de genótipos de milho quando submetidos a níveis contrastantes de nitrogênio.…”
Section: Resultsunclassified